STUDI EKSPERIMENTAL KINERJA BOILER MINI POWER PLANT P3TKEBTKE DEPT. ESDM RI - , YRVAN JOVA SEPTA DEVA, Fauzun, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Boiler performance is determined by calculation of the efficiency that has been done, either by the direct method or the indirect method. The higher boiler efficiency the better its performance. This study was focused in analyzing performance of mini power plant boiler Center of Research and Development of Electricity Technology, New and Renewable Energy and Energy Conservation (P3TKEBTKE) ESDM, which use biomass as fuel. The fuel used was coconut shell charcoal which was varied itâs mass flowrate, that is 15 kg / h, 20 kg / h, 30 kg / h and 60 kg / h with a constant mass flowrate of air 2304 kg / h. The pressure also varied into 3 variants, 3 barsg, 4 barsg and 5 barsg and the mass of water in the water drum boiler to be 25%, 50% and 75% volume. The objective of the analysis was to identify the resulting efficiency of the combustion process to the boiler. The results showed that the efficiency of the boiler to increase as increasing the air fuel ratio and operating pressure. While the volume of water in the drum has no effect on the efficiency of the boiler. Combustion chamber temperatures fluctuated.